2005
DOI: 10.2337/diacare.28.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Is Associated With Increased Cyclooxygenase- and Cytokine-Mediated Inflammation

Abstract: OBJECTIVE -The extent of involvement of cyclooxygenase (COX)-mediated inflammation in type 1 diabetes is unknown, and the association between the COX-and cytokine-mediated inflammatory responses in type 1 diabetes is not fully understood.RESEARCH DESIGN AND METHODS -Plasma high-sensitivity C-reactive protein (CRP), 24-h urinary and plasma 15-keto-dihydro-prostaglandin F 2␣ (a metabolite of prostaglandin F 2␣ [PGF 2␣ ] and an indicator of COX-mediated inflammation), serum amyloid protein A (SAA), and interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 34 publications
3
42
2
2
Order By: Relevance
“…Previous studies have reported that the elevation of pro-and anti-inflammatory cytokine levels is linked to higher risk of diabetes development [39][40][41]. We extend these observations as we describe that in addition of BMI, diabetes type is associated with systemic cytokine concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have reported that the elevation of pro-and anti-inflammatory cytokine levels is linked to higher risk of diabetes development [39][40][41]. We extend these observations as we describe that in addition of BMI, diabetes type is associated with systemic cytokine concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, SAA may also be a very important molecule in T1D and its complications. Although the mean SAA level in the plasma of 38 T1D patients was not different from the mean level in 41 control subjects measured in a previous study (20), the current study with 1139 T1D patients and 848 controls revealed significantly higher SAA levels in T1D patients. Although SAA and CRP levels in serum are correlated (Fig.…”
Section: Discussioncontrasting
confidence: 93%
“…Type 1 diabetes mellitus is associated with increased cytokine-mediated inflammation [5]. In agreement with our results it has been shown that components of the endothelial glycocalyx are shed in response to inflammation [6].…”
supporting
confidence: 81%